A Quantitatively Comparative Study on Green Pattern of Urban Park in Beijing, London, Paris and New York Using Spatial Statistics Model. Issue 5 (May 2019) - Xin, Yang; Rui, Liu; MeiTing, Su
Abstract: This paper comparatively analyzed green pattern content of Beijing, London and Paris, New York with three spatial statistical models: average nearest neighbor analysis method, weighted standard deviation ellipse method and kernel density method to achieve scientific and accurate data analysis. The paper analyzed aggregation level and distribution of urban parks, area distribution of urban parks and green pattern overall model analysis of four cities. Finally, three analysis methods of spatial statistical models provided new ideas for research on urban green space pattern and effectively realized scientific and refined research of green pattern.